Zero-deformation totally-enclosed graphene / oxide composite metal lithium negative electrode with laminated pore cavity microstructure and preparation and application thereof
Through the microstructure of the laminated pore cavity and the fully enclosed graphene/oxide composite metal lithium negative electrode, the volume change and high reactivity problems in the lithium deposition and peeling process in lithium metal batteries are solved, and high-efficiency lithium deposition and peeling are achieved. , improving the cycle reversibility and Coulomb efficiency of lithium metal batteries.
Patent Information
- Application Number
- CN202411029140.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-07-30
- Publication Date
- 2024-12-20
- Estimated Expiration
- 2044-07-30
AI Technical Summary
The volume changes in the existing lithium metal negative electrode during deposition and peeling lead to interfacial fracture and high reactivity, limiting the cyclic reversibility and Coulomb efficiency of lithium metal batteries.
Using the microstructure of laminated pore cavity, zero deformation, fully enclosed graphene/oxide composite metal lithium negative electrode, the oxide layer is deposited on the surface and interior of the rGO film by atomic layer deposition method, to limit the deposition of lithium in the laminated pore cavity and Peel to avoid corrosion of the electrolyte.
The lithium deposition and peeling efficiency of up to 2000 turns in lithium metal batteries was achieved, which significantly improved the cycle reversibility performance and Coulomb efficiency, and avoided volume changes and interface damage.
Smart Images

Figure HDA0004969431610000011 
Figure HDA0004969431610000012 
Figure HDA0004969431610000013
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of high-energy-density lithium metal batteries, and specifically relates to a laminated pore microstructure, zero deformation, fully enclosed graphene / oxide composite metal lithium negative electrode, and its preparation and application. Background Art
[0002] Lithium metal (Li) has a high theoretical capacity (3,860 mAh g -1 ), the lowest electrochemical redox potential (-3.04V vs. SHE), and is considered to be the ultimate negative electrode material to replace graphite negative electrodes in high-energy-density rechargeable batteries. However, the poor coulombic efficiency of the metal lithium negative electrode in high-energy-density metal lithium batteries leads to problems such as battery capacity decay, rapid loss of active materials and short cycle life. In addition, it is difficult for lithium metal negative electrodes to achieve a coulombic efficiency greater than 99.9% in 1000 cycles, which seriously limits the development of lithium metal battery technology.
[0003] There are two difficult problems with the current lithium metal anode: the difficult-to-control volume change of the lithium metal anode during lithium deposition and stripping, and the high reactivity of metal lithium with the electrolyte. Many studies have shown that the high reactivity of metal lithium with the electrolyte can be partially improved by constructing an artificial solid electrolyte membrane (SEI), optimizing electrolyte components, and developing solid electrolytes. Many research teams have also partially alleviated the volume change problem of the lithium metal anode during lithium deposition and stripping by introducing three-dimensional frameworks, but the open main framework also has a large surface area of lithium metal anode exposed to the electrolyte, which will inevitably produce side reactions, and it is still impossible to completely overcome the volume change problem of lithium metal during the deposition-dissolution process. At present, there has never been any report in the world that can completely solve the volume change problem of metal lithium anode, which is the fundamental reason for the poor cycle reversibility and low coulomb efficiency of contemporary lithium metal anodes.
[0004] Therefore, how to reduce the volume change mechanism during the lithium metal anode deposition-dissolution electrochemical reaction from a relatively infinite volume change to zero while avoiding exposure of lithium metal to corrosive electrolytes will be an effective way to achieve a lithium deposition / stripping efficiency greater than 99.9% and realize a highly reversible lithium metal anode. Summary of the invention
[0005] In view of the shortcomings of the prior art, the present invention provides a laminated pore microstructure, zero deformation, fully enclosed graphene / oxide composite metal lithium negative electrode and its preparation and application. The laminated pore microstructure in the composite metal lithium negative electrode material of the present invention is the key to changing the working principle of the metal lithium negative electrode. The structure limits the lithium to be deposited and stripped inside the laminated pores, avoiding the interface fracture caused by volume change; and the two-dimensional continuous rGO composite inorganic oxide completely avoids the electrolyte penetration and corrosion of lithium metal; for the first time, a lithium deposition and stripping efficiency of 99.99% to 99.999% for up to 2000 cycles in lithium metal batteries is achieved, which has great application prospects.
[0006] The technical solution adopted by the present invention is as follows:
[0007] A method for preparing a laminated pore microstructure, zero deformation, and fully enclosed graphene / oxide composite metal lithium negative electrode comprises the following steps:
[0008] (1) GO thin film is prepared by drying GO aqueous dispersion;
[0009] (2) GO film is reduced to obtain rGO film;
[0010] (3) Oxides are loaded on the surface and inside of the rGO film to obtain oxide composite rGO film;
[0011] (4) The oxide composite rGO film is loaded with metallic lithium to obtain a laminated pore microstructure, zero deformation, and fully enclosed graphene / oxide composite metallic lithium negative electrode.
[0012] Preferably, according to the present invention, in step (1), the mass concentration of the GO aqueous dispersion is 1-100 mg / g.
[0013] Preferably according to the present invention, in step (1), the drying temperature is 20-100°C.
[0014] Preferably according to the present invention, in step (1), the thickness of the GO film is 10-500 μm.
[0015] According to the preferred embodiment of the present invention, in step (1), the method for preparing the GO film comprises the steps of: uniformly coating the GO aqueous dispersion on a mold, and obtaining the GO film by drying. Preferably, the mold is a quartz glass plate.
[0016] According to the preferred embodiment of the present invention, in step (2), the preparation method of the rGO film comprises the steps of: reducing the GO film with a reducing agent or high-temperature heat treatment to obtain the rGO film; wherein the reducing agent is a 5wt%-50wt% aqueous solution of hydrogen iodide, a 5wt%-50wt% aqueous solution of sodium ascorbate or hydrazine hydrate vapor; the mass ratio of the reducing agent to the GO film is 0.5-5:1, the reduction reaction temperature is 50-500°C, and the reduction reaction time is 1-48h; the high-temperature heat treatment temperature is 100-3000°C, the high-temperature heat treatment atmosphere is nitrogen or argon, and the high-temperature heat treatment time is 0.01-1000 minutes. Preferably, the high-temperature heat treatment temperature is 250-350°C, and the high-temperature heat treatment time is 0.01-1 minute.
[0017] Preferably, in step (2), after the reduction reaction, a rolling step is further performed to make the thickness of the rGO film be 1-300 μm.
[0018] Preferably according to the present invention, in step (3), the oxide is ZnO, Al2O3, TiO2, MoO2 or Co2O3.
[0019] Preferably according to the present invention, in step (3), the method for preparing the oxide composite rGO film comprises the steps of: depositing a 10-500 nm thick oxide layer on the surface and inside of the rGO film by atomic layer deposition to obtain an oxide composite rGO film; preferably, the thickness of the oxide layer is 70-300 nm, and further preferably 225-300 nm.
[0020] According to the preferred embodiment of the present invention, in step (4), the method for preparing a laminated pore microstructure, zero deformation, and fully enclosed graphene / oxide composite metal lithium negative electrode comprises the steps of: contacting the edges of the oxide composite rGO film, melting metal lithium for 0.5-10s, and then standing at 250-450°C for 5-30 minutes to allow the metal lithium to diffuse evenly into the oxide composite rGO film, thereby obtaining a laminated pore microstructure, zero deformation, and fully enclosed graphene / oxide composite metal lithium negative electrode. Since the oxide composite rGO film has a large number of nanopores and a lithium-philic oxide layer inside, the molten metal lithium will diffuse evenly into the oxide composite rGO film according to capillary action.
[0021] A laminated pore microstructure, zero deformation, and fully enclosed graphene / oxide composite metal lithium negative electrode is prepared by the above method.
[0022] Preferably according to the present invention, the graphene / oxide composite metal lithium negative electrode is an oxide composite rGO film with a laminated pore microstructure with internal cavity loaded with metal lithium; the oxide composite rGO film with a laminated pore microstructure is an rGO film with a laminated pore microstructure with oxide loaded on the surface and inside.
[0023] The above-mentioned laminated pore microstructure, zero deformation, and fully enclosed graphene / oxide composite metal lithium negative electrode are used in lithium metal batteries.
[0024] According to the preferred embodiment of the present invention, the positive electrode of the lithium metal battery is lithium cobalt oxide, a ternary nickel-cobalt-manganese layered material, lithium iron phosphate, lithium titanate, a layered lithium-rich manganese-based positive electrode material or a layered lithium manganese oxide (LiMnO2); the diaphragm is selected from glass carbon fiber, a polypropylene diaphragm or a polyethylene diaphragm; the solute of the electrolyte is selected from one or a combination of two or more of lithium hexafluorophosphate, lithium bis(trifluoromethylsulfonyl)imide, lithium nitrate or lithium polysulfide, and the solvent of the electrolyte is selected from one or a combination of two or more of 1,3-dioxolane, ethylene glycol dimethyl ether, triethylene glycol dimethyl ether, diethyl carbonate, 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether, 1,1,2,3,3,3-hexafluoropropyl-2,2,2-trifluoroethyl ether or 1,1,1,2,2,3,4,5,5,5-decafluoropentane; the lithium metal battery packaging includes a button battery case, a soft pack battery case or a stainless steel battery case.
[0025] The technical features and beneficial effects of the present invention are as follows:
[0026] (1) The present invention adopts the method of atomic layer vapor deposition, which can evenly load the oxide layer onto the surface and interior of rGO, not just on the surface of rGO. The oxide coating can enhance the ionic conductivity of the composite negative electrode and the lithium ion transmission capacity, and has the advantages of uniform oxide layer thickness, high stability, and large-scale preparation.
[0027] (2) The laminated pore microstructure in the composite metal lithium negative electrode material of the present invention is the key to changing the working principle of the metal lithium negative electrode. This structure limits the lithium to be deposited and peeled off inside the laminated pores, completely suppressing the volume change and interface damage problems during the deposition and dissolution of the lithium metal negative electrode; and the two-dimensional continuous rGO composite inorganic oxide completely avoids the side reactions caused by the electrolyte penetration and corrosion of lithium metal.
[0028] (3) In summary, the laminated pore microstructure, zero deformation, and fully enclosed graphene / oxide composite metal lithium negative electrode prepared by the present invention has the advantages of high specific energy and long life. In addition, this in-situ constructed component and thickness-adjustable electrode material is applied to lithium metal batteries, which significantly improves the cycle reversibility and coulombic efficiency of lithium metal batteries, and achieves a lithium deposition / stripping efficiency of 99.99% to 99.999% for up to 2000 cycles in lithium metal batteries, which has great application prospects. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 SEM images of the composite metal lithium negative electrodes prepared in Example 1(a) and Comparative Example 1(b);
[0030] Figure 2 The half-cell cycle performance of the composite metal lithium negative electrode prepared in Example 1 and Comparative Example 1;
[0031] Figure 3 The full battery cycle performance of the composite metal lithium negative electrode prepared in Example 1 and Comparative Example 1;
[0032] Figure 4 The SEM images of the full battery of the composite metal lithium negative electrode prepared in Example 1 and Comparative Example 1 under different cycle states;
[0033] Figure 5 X-ray photoelectron spectroscopy depth etching images of the composite metal lithium negative electrode prepared in Example 1 and Comparative Example 1 after full battery cycling;
[0034] Figure 6 This is an in-situ pressure test diagram of the soft-pack battery with composite metal lithium negative electrode prepared in Example 1 and Comparative Example 1. DETAILED DESCRIPTION
[0035] The present invention is further explained and illustrated below in conjunction with the accompanying drawings and specific embodiments. This embodiment is implemented on the premise of the technical solution of the present invention, and a detailed implementation method and specific operation process are given, but the protection scope of the present invention is not limited to the following embodiments.
[0036] Example 1
[0037] A method for preparing a laminated pore microstructure, zero deformation, and fully enclosed graphene / oxide composite metal lithium negative electrode comprises the following steps:
[0038] Step 1: Preparation of GO film: Use a quartz glass plate to evenly coat a 10 mg / g GO aqueous solution on the glass plate, and dry it naturally at room temperature to obtain a GO film with a thickness of 300 μm.
[0039] Step 2, preparation of rGO film: Place the GO film on a high-temperature heating table at 300°C for 1 second in a glove box filled with argon. After a large number of oxygen functional groups in GO are removed, an rGO film with a laminated pore microstructure is obtained. After rolling, an rGO film with a thickness of about 50 μm is obtained.
[0040] Step 3. ZnO film is plated on the surface and inside of the rGO film: The rGO film with a laminated cavity microstructure is placed in a chamber at 150°C and deposited for 800 cycles using an atomic layer deposition (ALD) device. A 300nm thick ZnO film is deposited on the surface and inside of the rGO film to obtain a ZnO composite rGO film with a laminated cavity microstructure.
[0041] Step 4: Prepare a lithium metal composite negative electrode: heat lithium foil on a high-temperature heating table at 350°C to obtain molten lithium, and contact the edge of the ZnO composite rGO film with a laminated pore microstructure obtained in step 3 with molten metallic lithium for 5 seconds, and then place it in a heating chamber at 300°C for 15 minutes to allow lithium to diffuse evenly into the interior of the composite film. The metallic lithium is stored in the ZnO composite rGO cavity, and then cooled to room temperature to obtain a laminated pore microstructure, zero deformation, and fully enclosed graphene / oxide composite metallic lithium negative electrode, i.e., a two-dimensional continuous Li@rGO&ZnO.
[0042] Step 5: Assembly of lithium metal battery: The obtained Li@rGO&ZnO composite support was used as the negative electrode, and the battery was assembled with a commercial ternary nickel-cobalt-manganese layered positive electrode (LiNi5Co2Mn3O2(NCM523)), Celgard2325 separator, and a local high-concentration electrolyte (molar ratio of LiFSI:DME:TTE=1:1.2:3). The specific capacity of the positive electrode was 3.06 mAh cm -2 , the full battery negative electrode: positive electrode capacity ratio (R N / P ) is 2.3, thereby obtaining a lithium metal CR2032 button cell, i.e., a NCM523 full cell.
[0043] Example 2
[0044] A method for preparing a laminated pore microstructure, zero deformation, and fully enclosed graphene / oxide composite metal lithium negative electrode is as described in Example 1, except that: in step three, ZnO is replaced by Al2O3; the specific steps are as follows: using atomic layer deposition (ALD) equipment, 300nm Al2O3 film is deposited on the surface and inside of the rGO film to obtain an Al2O3 composite rGO film with a laminated pore microstructure.
[0045] The remaining steps and conditions are the same as in Example 1.
[0046] Example 3
[0047] A method for preparing a laminated pore microstructure, zero deformation, and fully enclosed graphene / oxide composite metal lithium negative electrode is as described in Example 1, except that: in step three, ZnO is replaced by TiO2; the specific steps are as follows: using atomic layer deposition (ALD) equipment, a 300nm TiO2 film is deposited on the surface and inside of the rGO film to obtain a TiO2 composite rGO film with a laminated pore microstructure.
[0048] The remaining steps and conditions are the same as in Example 1.
[0049] Example 4
[0050] A method for preparing a laminated pore microstructure, zero deformation, and fully enclosed graphene / oxide composite metal lithium negative electrode is as described in Example 1, except that: in step three, ZnO is replaced by Co2O3; the specific steps are as follows: using an atomic layer deposition (ALD) device, a 300nm Co2O3 film is deposited on the surface and inside of the rGO film to obtain a Co2O3 composite rGO film with a laminated pore microstructure.
[0051] The remaining steps and conditions are the same as in Example 1.
[0052] Example 5
[0053] A method for preparing a laminated pore microstructure, zero deformation, and fully enclosed graphene / oxide composite metal lithium negative electrode is as described in Example 1, except that: in step three, an atomic layer deposition (ALD) device is used to place an rGO film with a laminated pore microstructure in a chamber at 150° C. and deposit 200 cycles, and a 75nm ZnO film is deposited on the surface and inside of the rGO film to obtain a ZnO composite rGO film with a laminated pore microstructure.
[0054] The remaining steps and conditions are the same as in Example 1.
[0055] Example 6
[0056] A method for preparing a laminated pore microstructure, zero deformation, and fully enclosed graphene / oxide composite metal lithium negative electrode is as described in Example 1, except that: in step three, an atomic layer deposition (ALD) device is used to place an rGO film with a laminated pore microstructure in a chamber at 150° C. and deposit 400 cycles, and a 150nm ZnO film is deposited on the surface and inside of the rGO film to obtain a ZnO composite rGO film with a laminated pore microstructure.
[0057] The remaining steps and conditions are the same as in Example 1.
[0058] Example 7
[0059] A method for preparing a laminated pore microstructure, zero deformation, and fully enclosed graphene / oxide composite metal lithium negative electrode is as described in Example 1, except that: in step three, an atomic layer deposition (ALD) device is used to place an rGO film with a laminated pore microstructure in a chamber at 150° C. and deposit 600 cycles, and a 225nm ZnO film is deposited on the surface and inside of the rGO film to obtain a ZnO composite rGO film with a laminated pore microstructure.
[0060] The remaining steps and conditions are the same as in Example 1.
[0061] Comparative Example 1
[0062] A method for preparing a structurally destroyed composite metal lithium negative electrode is as described in Example 1, except that step (iii) is omitted, the rGO film obtained in step (ii) is directly used to load metal lithium, and then the structure is completely destroyed using a cell disruptor to obtain a structurally destroyed composite metal lithium negative electrode; the specific steps are as follows:
[0063] The preparation of GO film is the same as step (i) of Example 1;
[0064] The preparation of rGO film is the same as step (ii) of Example 1;
[0065] Step 3: Prepare lithium metal composite negative electrode: Heat lithium foil on a high temperature heating table at 350°C to obtain molten lithium, contact the edge of the rGO film obtained in step 2 with the molten metal lithium for 5s, then place it in a heating chamber at 300°C for 15 minutes to allow lithium to diffuse evenly into the rGO film, and then cool it to room temperature to obtain a composite metal lithium negative electrode. Use a cell disruptor to completely destroy the structure to obtain a structurally destroyed composite metal lithium negative electrode (random Li@rGO&ZnO).
[0066] The assembly method of the lithium metal CR2032 button cell is the same as step (v) of Example 1.
[0067] Test Example 1
[0068] (1) SEM of the composite metal lithium negative electrode prepared in Example 1 and Comparative Example 1 was tested.
[0069] like Figure 1 As shown, both Example 1 and Comparative Example 1 have a thickness of 50 μm, but the difference is that Example 1 has a regular layered structure, while Comparative Example 1 has no layered structure, which is caused by the destruction of the structure when preparing the sample.
[0070] (2) Half-cell battery performance test
[0071] The composite metal lithium negative electrode prepared in Example 1, Examples 5-7 or Comparative Example 1 is used as the negative electrode, and the electrolyte is a local high-concentration electrolyte (molar ratio of LiFSI:DME:TTE=1:1.2:3) to construct a half-cell.
[0072] Depend on Figure 2 By comparison, it can be seen that the Li|| composite negative electrode half-cell of Example 1 and Comparative Example 1 has a high -2 The current density and 1 mAh cm -2 The cycles were carried out at a surface capacity of , and the average coulombic efficiency of Example 1 at a cycle number of about 2000 cycles was maintained at about 99.99%-99.999%, and the average coulombic efficiency of Comparative Example 1 at a cycle number of about 900 cycles was about 95.05435%.
[0073] From the comparison in Table 1, it can be seen that the composite negative electrodes with different deposition cycles have different half-cell coulombic efficiencies.
[0074] Table 1 Coulombic efficiency of half-cells of composite negative electrodes with different deposition cycles
[0075] Number of deposition cycles Half-cell coulombic efficiency (first 200 cycles) 200 (Example 5) 99.23% 400 (Example 6) 99.44% 600 (Example 7) 99.59% 800 (Example 1) 99.99%
[0076] (3) Full battery performance test
[0077] The performance of the NCM523 full batteries prepared in Example 1 and Comparative Example 1 were tested.
[0078] Depend on Figure 3 By comparison, it can be seen that the capacity retention rate of Example 1 under the full battery cycle of about 700 cycles at 0.5C is 89%, while the capacity retention rate of Comparative Example 1 under the cycle of 136 cycles at 0.5C is maintained at 80%.
[0079] (4) Next, the sample thicknesses of Example 1 and Comparative Example 1 were compared. The composite negative electrode of the half-cell constructed in (2) at different cycle states was photographed using a scanning electron microscope. Figure 4 It can be seen from ae that Example 1 has a -2 The thickness after Li stripping and deposition remains unchanged at 50 μm, and at 1 mAh cm -2 The thickness did not change after 400 cycles. Figure 4 fj shows that comparative example 1 is 1 mAh cm -2 The thickness after Li deposition and stripping changes to 18.9 μm / 25.1 μm, respectively (the change rate compared to the original thickness is 62.2% / 49.8%, respectively).
[0080] (5) Construct a half-cell according to the method in (2); at 1 mAh cm -2 Li is stripped off and the negative electrode samples are stripped using ion beam etching with different etching times. The X-ray photoelectron spectroscopy depth etching diagram shows ( Figure 5), Example 1 shows a double-layer SEI structure, in which the outer layer is composed of organic matter derived from the electrolyte, and the inner layer is converted from lithiated 0VCCS rGO&ZnO (a special graphene zinc oxide composite material), which is an inorganic substance. The SEI layer of Comparative Example 1 shows a distribution pattern dominated by organic components derived from the electrolyte throughout the thickness range, which is rich in organic carbon and fluorine-based components derived from the electrolyte, which is in sharp contrast to the SEI constructed by lithiated 0VCCS rGO&ZnO, which has better stability and ability to isolate the electrolyte. This shows that the electrolyte cannot penetrate the continuous two-dimensional SEI layer formed in Example 1. This means that this SEI structure can remain stable and will not break even during the process of large-scale lithium deposition and stripping.
[0081] (6) The composite negative electrode of Example 1 or Comparative Example 1, the commercial lithium titanate positive electrode, the Celgard 2325 separator, and the local high concentration electrolyte (molar ratio of LiFSI:DME:TTE=1:1.2:3) were assembled into a soft pack battery. The soft pack battery was subjected to an in-situ pressure test. Figure 6 By comparison, it can be seen that the pressure of Example 1 during the deposition and stripping of lithium remains unchanged and is maintained at about 440 KPa, indicating that Example 1 has well achieved zero volume change; the comparative example 1 has a huge pressure change during the deposition and stripping of lithium, indicating that the lithium negative electrode has undergone a volume change during the deposition and dissolution process, and the solid electrolyte interface has ruptured, exposing the metallic lithium to a side reaction with the electrolyte, which is also the reason for the low coulombic efficiency and rapid capacity decay.
[0082] In summary, the present invention provides a method for preparing a rGO and inorganic oxide composite metal lithium negative electrode material with a laminated pore microstructure and zero deformation and fully closed characteristics, and its application in lithium metal batteries, thereby achieving a lithium deposition / stripping efficiency of 99.99% to 99.999% for up to 2000 cycles in lithium metal batteries, which has great application prospects.
[0083] The above description is only a preferred embodiment of the present invention, and the implementation of the present invention is not limited to the above embodiment. Any modifications, equivalent substitutions, improvements, etc. made by technicians in this field within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing a laminated pore microstructure, zero deformation, and fully enclosed graphene / oxide composite metal lithium negative electrode, comprising the steps of: (1) GO thin film is prepared by drying GO aqueous dispersion; (2) GO film is reduced to obtain rGO film; (3) Oxides are loaded on the surface and inside of the rGO film to obtain oxide composite rGO film; (4) The oxide composite rGO film is loaded with metallic lithium to obtain a laminated pore microstructure, zero deformation, and fully enclosed graphene / oxide composite metallic lithium negative electrode.
2. The method for preparing the laminated pore microstructure, zero deformation, fully enclosed graphene / oxide composite metal lithium negative electrode according to claim 1, characterized in that: In step (1), one or more of the following conditions are included: i. The mass concentration of GO aqueous dispersion is 1-100 mg / g; ii. Drying temperature is 20-100℃; iii. The thickness of the GO film is 10-500 μm; iii. The method for preparing a GO film comprises the steps of: uniformly applying a GO aqueous dispersion on a mold, and obtaining a GO film by drying; preferably, the mold is a quartz glass plate.
3. The method for preparing the laminated pore microstructure, zero deformation, fully enclosed graphene / oxide composite metal lithium negative electrode according to claim 1, characterized in that: In step (2), the preparation method of the rGO film comprises the following steps: the GO film is reduced by a reducing agent or subjected to high-temperature heat treatment to obtain the rGO film; wherein the reducing agent is a 5wt%-50wt% aqueous solution of hydrogen iodide, a 5wt%-50wt% aqueous solution of sodium ascorbate or hydrazine hydrate vapor; the mass ratio of the reducing agent to the GO film is 0.5-5:1, the reduction reaction temperature is 50-500°C, and the reduction reaction time is 1-48h; the high-temperature heat treatment temperature is 100-3000°C, the high-temperature heat treatment atmosphere is nitrogen or argon, and the high-temperature heat treatment time is 0.01-1000 minutes; preferably, the high-temperature heat treatment temperature is 250-350°C, and the high-temperature heat treatment time is 0.01-1 minute.
4. The method for preparing the laminated pore microstructure, zero deformation, fully enclosed graphene / oxide composite metal lithium negative electrode according to claim 1, characterized in that: In step (2), a rolling step is further included after the reduction reaction, so that the thickness of the rGO film is 1-300 μm.
5. The method for preparing the laminated pore microstructure, zero deformation, fully enclosed graphene / oxide composite metal lithium negative electrode according to claim 1, characterized in that: In step (3), the oxide is ZnO, Al2O3, TiO2, MoO2 or Co2O3.
6. The method for preparing the laminated pore microstructure, zero deformation, fully enclosed graphene / oxide composite metal lithium negative electrode according to claim 1, characterized in that: In step (3), the method for preparing the oxide composite rGO film comprises the steps of: using atomic layer deposition to deposit an oxide layer with a thickness of 10-500 nm on the surface and inside of the rGO film to obtain the oxide composite rGO film.
7. The method for preparing the laminated pore microstructure, zero deformation, fully enclosed graphene / oxide composite metal lithium negative electrode according to claim 1, characterized in that: In step (4), the method for preparing a laminated pore microstructure, zero deformation, and fully enclosed graphene / oxide composite metal lithium negative electrode includes the steps of: contacting the edges of the oxide composite rGO film with molten metal lithium for 0.5-10s, and then standing at 250-450°C for 5-30 minutes to allow the metal lithium to evenly diffuse into the interior of the oxide composite rGO film, thereby obtaining a laminated pore microstructure, zero deformation, and fully enclosed graphene / oxide composite metal lithium negative electrode.
8. A laminated pore microstructure, zero deformation, fully enclosed graphene / oxide composite metal lithium negative electrode, prepared by any one of the methods of claims 1-7.
9. The laminated pore microstructure, zero deformation, fully enclosed graphene / oxide composite metal lithium negative electrode according to claim 8, characterized in that: The graphene / oxide composite metal lithium negative electrode is an oxide composite rGO film with a laminated pore microstructure with metal lithium loaded in the inner cavity; the oxide composite rGO film with a laminated pore microstructure is an rGO film with a laminated pore microstructure with oxide loaded on the surface and inside.
10. Application of the laminated pore microstructure, zero deformation, fully enclosed graphene / oxide composite metal lithium negative electrode as claimed in claim 8 in lithium metal batteries.
Citation Information
Patent Citations
Preparation method of graphene / manganese oxide composite material
CN107706374A
Preparation method of anti-bending lithium metal negative electrode
CN108448065A
Ultra-thin metal lithium complex, preparation method and application thereof
CN109873122A
Metal lithium composite negative electrode capable of being used for secondary battery and preparation method of metal lithium composite negative electrode
CN115832217A
Ultrathin efficient graphene composite film-based lithium carrier and application thereof in lithium metal battery
CN116936751A
Cited By
Laminated structure porous intelligent flame-retardant skeleton composite metal lithium negative electrode and preparation and application thereof
CN120048848A
A laminated porous intelligent flame-retardant skeleton composite metal lithium negative electrode and its preparation and application
CN120048848B
